Internet Usage and its effect on Senior High School Students in Bantama Sub-Metro in Kumasi Metropolis of Ghana - Kwaah, C.O.; Ankrah, E.; Frimpong, A.D.; et al. (My University, 2021)
The internet has become the fountain of information access for senior high school students and academics. Poor telecommunication infrastructure, difficulties in accessing relevant information, inadequate computers, high cost of bundles, system failure, low internet bandwidth, and power fluctuation are some challenges Senior High students face in their quest to access information on the internet. The study sought to determine internet usage and its effect on students of three Senior High schools in the Bantama Sub-Metro in the Kumasi Metropolis. The study adopted the survey research design, and the quantitative research approach was used; hence questionnaires were the main instrument employed for data collection. A total of 360 students were conveniently sampled from three selected Senior High schools. From the results, it was found that students accessed information on the internet prominently for communication, recreation, and learning. The public internet café was the highest point of internet access followed by the home and availability of computer laboratories in the schools. However, confirming the effects on students regarding the use of the internet, the students were given limited hours to access information and different internet infrastructure in the schools. The majority of the students rated the internet access in their school computer laboratories as poor. By implication, Administrators and parents should adopt safety measures to monitor the internet content used by students, educating students on how to access and use information from the internet, provision of more computers in the school's laboratories, and high bandwidth to access the internet.
Research Article
Keywords: Internet Use; Senior High Schools; Bantama Sub-Metro; Computer Laboratory; Kumasi Metropolis